Flavonoids are identified from the extract of Scutellariae Radix to suppress inflammatory-induced angiogenic responses in cultured RAW 264.7 macrophages. Issue 1 (December 2018) - Gong, Guowei; Wang, Huaiyou; Kong, Xiangpeng; Duan, Ran; Dong, Tina; Tsim, Karl
Abstract Scutellariae Radix (SR), also named Huangqin in China, is the dried root ofScutellaria baicalensis Georgi. Historically, the usage of SR was targeted to against inflammation. In fact, chronic inflammation has a close relationship with hypoxia and abnormal angiogenesis in tumor cells. Hence, we would like to probe the water extract of SR in suppressing the inflammation-induced angiogenesis. Prior to determine the pharmaceutical values of SR, the first step is to analysis the chemical compositions of SR according to China Pharmacopeia (2015). From the results, the amount of baicalin was 12.6% by weight. Furthermore, the anti-angiogenic properties of SR water extract were evaluated in lipopolysaccharide (LPS) pre-treated cultured macrophage RAW 264.7 cells by detecting the inflammatory markers, i.e. Cox-2, cytokine and iNOS, as well as the translocation activity of NFκB and angiogenic biomarker, i.e. VEGF. This herbal extract was capable of declining both inflammatory and angiogenic hallmarks in a concentration-dependent manner. Moreover, the SR-derived flavonoids, i.e. baicalin, baicalein, wogonin and wogonoside, were shown to be active chemicals in the anti-inflammatory-induced angiogenesis. Therefore, the inflammation-induced angiogenesis is believed to be suppressed by SR water extract, or its major ingredients. These results shed light in the benefiting role of SR in the inflammation-induced angiogenesisin vitro .